Developing JAMPI as a Jamu-Based Local Wisdom Learning Kit to Improve Sustainable Living Literacy in Elementary Character Education - Marni, Marni; Elhawwa, Tazkiyatunnafs; Riadin, Agung Riadin (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
This study aimed to develop and evaluate JAMPI (Jamu Alami Media Pembelajaran Inovatif) as a jamu-based local wisdom learning kit to improve sustainable living literacy in the Character Education theme for Grade 5 students at SDN 11 Baamang Tengah, Central Kalimantan. The study responded to the limited availability of contextual instructional media that integrate local medicinal plant knowledge, sustainability concepts, and character formation in elementary classrooms. A Research and Development design was applied using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The field implementation involved one intact Grade 5 classroom consisting of 24 students. Data were collected through needs analysis, expert validation, teacher and student response questionnaires, pre-test and post-test, character observation, interviews, and documentation. The JAMPI product consisted of a teacher guidebook, student activity book, medicinal plant information cards, practical jamu-making kit, and infographic posters. The expert validation result showed that JAMPI was feasible, with an average score of 79.41%. The practicality test showed highly feasible results, with teacher response reaching 87.5% and student response reaching 89.2%. The effectiveness test showed that students’ average score increased from 45.54 in the pre-test to 90.25 in the post-test, with an N-Gain of 0.82 in the high category. Student character scores also increased from 63.8% to 85.3%. These findings indicate that JAMPI effectively supports sustainable living literacy, cultural appreciation, environmental responsibility, and character development through concrete, experiential, and locally grounded learning.